Patient Safety and Quality Improvement in Otolaryngology Education: A Systematic Review. (June 2017) - Gettelfinger, John D.; Paulk, P. Barrett; Schmalbach, Cecelia E.
Objective: The breadth and depth of patient safety/quality improvement (PS/QI) research dedicated to otolaryngology–head and neck surgery (OHNS) education remains unknown. This systematic review aims to define this scope and to identify knowledge gaps as well as potential areas of future study to improved PS/QI education and training in OHNS. Data Sources: A computerized Ovid/Medline database search was conducted (January 1, 1965, to May 15, 2015). Similar computerized searches were conducted using Cochrane Database, PubMed, and Google Scholar. Review Methods: The study protocol was developed a priori using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Articles were classified by year, subspecialty, Institute of Medicine (IOM) Crossing the Chasm categories, and World Health Organization (WHO) subclass. Results: Computerized searches yielded 8743 eligible articles, 267 (3.4%) of which met otolaryngology PS/QI inclusion criteria; 51 (19%) were dedicated to resident/fellow education and training. Simulation studies (39%) and performance/competency evaluation (23.5%) were the most common focus. Most projects involved general otolaryngology (47%), rhinology (18%), and otology (16%). Classification by the IOM included effective care (45%), safety/effective care (41%), and effective and efficient care (7.8%). Most research fell into the WHO category of "identifying solutions" (61%). Conclusion: Nineteen percent of OHNS PS/QI articles are dedicated to education, the majority of which are simulation and focus on effective care. Knowledges gaps for future research include facial plastics PS/QI and the WHO category of "studies translating evidence into safer care."